Distribuição espaço-temporal da Hanseníase em menores de 15 anos, na Amazônia Legal maranhense no período de 2011 – 2021 - PEREIRA, Débora Lorena Melo (2023)
Introduction: Leprosy, also known in antiquity as leprosy, is an infectious, chronic, slow and insidious disease, caused by the intracellular microorganism Mycobacterium leprae. Illness in childhood is less frequent, due to the long incubation period of the disease, the occurrence of leprosy in children under 15 years of age suggests the existence of bacilliferous household/family index cases, with strong indications of continuous and active transmission of the bacillus at home and in the community. Objective: to analyze the space-time distribution of leprosy cases in children under 15 years old in the municipalities of the Legal Amazon in Maranhão, from 2011 to 2021. Methods: an ecological study with a quantitative approach and the spatial pattern of leprosy cases in children under 15 years old years belonging to the municipalities of the Maranhão Legal Amazon during the period from 2011 to 2021. The municipalities of the Maranhão Amazon region were used as a unit of spatial analysis. Results: It was noted that in the period from 2011 to 2021, 3,236 cases were reported, the distribution of new cases in children under 15 years of age was considered high. The detection rate ranged from 9.24 to 23.60 with an average of 18.85/100 inhabitants being marked by oscillations in the years 2011, 2015 and 2017. male, brown, 10 to 14 years old, with incomplete primary education, multibacillary operational classification, borderline clinical form, and detection of degrees of disability. The thematic maps of the detection rate revealed the maintenance of high rates in most of the municipalities studied. Conclusion: the municipalities of Maranhão, belonging to the Legal Amazon, present, in a time frame from 2011 to 2021, an increase in the high rates of detection of leprosy in children under 15 years of age, with a prevalence of male, brown, 10 to 14-year-old cases, with incomplete primary education. The clinical forms that stood out were the borderline and tuberculoid and the multibacillary operational classification.